Knowledge, Attitude, and Practice of Nurses About Handling AntiNeoplastic Drugs at Hiwa Hospital in Sulaimaniyah, Iraq - Hussain, Barzan Hassan; Abdulkareem, Awayi Ghazy (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Anti-neoplastic drugs (ANDs) are a medical therapy utilized to fight cancer. Due to the possible health risks, safe handling and occupational exposure to anti-neoplastic agents have become significant concerns for oncology nursing staff. Objective: To assess the knowledge, attitude, and practice of nurses in handling ANDs at Hiwa Hematology/Oncology Hospital in Sulaimaniyah, Iraq. Materials and methods: A quantitative-descriptive cross-sectional design was carried out on 91 nurses working in Hiwa Hematology/Oncology Hospital from March to June 2022. A questionnaire was designed and constructed by the researcher. Results: The findings of this study showed that the higher percentages level of nurses' knowledge, attitude, and practice was 39.6%, 49.5%, and 51.6%, respectively, which indicated that the majority of participants in that hospital had a fair level of knowledge, attitude, and practice. A significant assertion was found between nurses' level of knowledge, attitude, and practice toward handling ANDs with age, employment status, years of experience in handling ANDs, receiving formal training, number of working hours per week, and exposure to an ANDs side effect. In addition, a highly significant association between nurses' level of knowledge, attitude, and practice toward handling ANDs (p=0.000) were found. Conclusion: We concluded that most of the sample had fair knowledge, attitude, and practice about handling ANDs, with a highly significant association.
Keywords: Handling antineoplastic drugs; knowledge; attitude; practices; nurses; cancer